2010
DOI: 10.1097/rct.0b013e3181d0f666
|View full text |Cite
|
Sign up to set email alerts
|

The Value of the Apparent Diffusion Coefficient in Differentiating Stage IA Endometrial Carcinoma From Normal Endometrium and Benign Diseases of the Endometrium

Abstract: The measurements of the ADC values have the potential to quantitatively differentiate stage IA endometrial carcinoma from normal endometrium and benign diseases of the endometrium. We propose adding DW imaging as an adjunct sequence in the routine MR protocol for the assessment of uterine lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 15 publications
2
19
1
1
Order By: Relevance
“…The accuracy of detecting myometrial invasion by endometrial cancer using T2-weighted images varies between 77% and 87% (3)(4)(5), whereas that using DCE is about 89%-91% (4,(6)(7)(8)(9). Recent reports suggest that the diagnostic accuracy of a combination of diffusionweighted imaging (DWI), T2WI, and DCE is more than that of imaging without DWI (10)(11)(12). However, preoperative MRI is still not a perfect imaging tool for analyzing cancers.…”
Section: Discussionmentioning
confidence: 95%
“…The accuracy of detecting myometrial invasion by endometrial cancer using T2-weighted images varies between 77% and 87% (3)(4)(5), whereas that using DCE is about 89%-91% (4,(6)(7)(8)(9). Recent reports suggest that the diagnostic accuracy of a combination of diffusionweighted imaging (DWI), T2WI, and DCE is more than that of imaging without DWI (10)(11)(12). However, preoperative MRI is still not a perfect imaging tool for analyzing cancers.…”
Section: Discussionmentioning
confidence: 95%
“…9). 12,18 On dynamic contrast-enhanced (DCE)-MRI, endometrial hyperplasia shows progressive enhancement, enhancing similar to or greater than adjacent myometrium. [12][13][14] Sometimes, small lowsignal-intensity cystic foci (cystic glandular dilatations) can be seen on delayed contrast-enhanced images.…”
Section: Benignmentioning
confidence: 99%
“…11,14 Polyps demonstrate less restricted diffusion than malignant lesions; Fujii et al 15 reported a mean apparent diffusion coefficient value of 1.44 Ϯ 0.34 for benign lesions and 0.98 Ϯ 0.19 for malignant lesions with an accuracy of 92%. [15][16][17][18] Endometrial polyps are typically removed to alleviate symptoms and to evaluate for atypical hyperplasia or carcinoma or both. [10][11][12] The risk of malignancy is related to polyp size and patient age.…”
Section: Benignmentioning
confidence: 99%
“…DWI imaging of endometrial tumors has decreased ADC values (108)(109)(110)(111)(112)(113)(114)(115)(116). Endometrial carcinoma is clearly depicted as an area of increased signal intensity relative to the surrounding hypointense myometrium on DWI (116).…”
Section: Female Pelvis Applicationsmentioning
confidence: 99%
“…Endometrial carcinoma is clearly depicted as an area of increased signal intensity relative to the surrounding hypointense myometrium on DWI (116). ADC measurements have the potential to quantitatively differentiate Stage IA endometrial carcinoma from normal endometrium, endometrial dysplasia and benign diseases of the endometrium, such as endometrial hyperplasia, adenomyosis, submucosal leiomyoma, and endometrial polyps (108)(109)(110)(111)(112)(113)(114)(115)(116). DWI and combined DWI/T2W MRI can increase the overall detection sensitivity for endometrial carcinoma (113).…”
Section: Female Pelvis Applicationsmentioning
confidence: 99%